Implementasi Iman Kristen Dalam Masyarakat: Analisis Wacana Film God’s Not Dead - Yuangga Kurnia Yahya (Institut Agama Kristen Negeri Toraja, 2020)
Abstract: This article discuss the religious realities that revealed in Trilogy of the film God 's Not Dead (2014), God' s Not Dead 2 (2016), and God 's Not Dead: A Light in Darkness (2018). This article is the result of a qualitative study using the Van Dijk’s discourse analysis approach. Discourse in movie is not enough to rely on the text simply because it consists of various structures and levels. The structure is macro structure, super structure, and micro structure.In the results of the study it was found that the preparation of discourse was quite structured, ranging from thematic structures, schematic structures, semantic structures, syntactic structures, stilistic structures, and rhetorical structures. Macro structure includes thematic structures, super structures include schematic structures, while the rest are included in the microstructure. The two elements of the structure show that this film does convey a real message that God still has a place in human life even though it lives in a very rational environment and does not involve God in their lives.Keywords: Theism, Christian Faith, Secularism, Film, Discourse Analysis. Abstrak: Artikel ini membahas tentang realitas keagamaan yang tampak dalam Trilogi film God’s Not Dead (2014), God’s Not Dead 2 (2016), dan God’s Not Dead: A Light in Darkness (2018). Artikel ini merupakan hasil dari studi kualitatif menggunakan pendekatan analisis wacana model Teun A Van Dijk. Wacana dalam film tidak cukup disandarkan pada teks semata karena ia terdiri dari berbagai struktur dan tingkatan. Struktur tersebut adalah struktur makro, super struktur, dan struktur mikro. Dari hasil penelitian ditemukan bahwa penyusunan wacana cukup terstruktur, mulai dari struktur Tematik, Struktur Skematik, Struktur Semantik, Struktur Sintaksis, Struktur Stilistik, dan struktur retorisnya. Struktur Makro meliputi struktur tematik, super struktur meliputi struktur skematik, adapun sisanya termasuk dalam struktur mikro. Kedua unsur dari struktur tersebut menunjukkan bahwa film ini memang menyampaikan pesan nyata bahwa Tuhan tetap memiliki tempat di kehidupan manusia meskipun hidup di lingkungan yang sangat rasional dan tidak melibatkan Tuhan dalam kehidupan mereka.Kata Kunci: Teisme, Iman Kristen, Film, Analisis Wacana.